2018
DOI: 10.1002/mop.31095
|View full text |Cite
|
Sign up to set email alerts
|

Parametric studies on hexagonal ring based aperture and patch type curved frequency selective surface

Abstract: Simulated and experimental investigations on hexagonal ring based aperture and patch type semi cylindrical curved frequency selective surfaces (FSSs) have been presented. Simulated and experimental results are in good agreement. Also, the parametric studies have been done for patch and aperture type Curved FSSs. Curved FSS structures are recently being investigated to design radome or nose of fighter aeroplane. This study will help the researchers to design curved frequency selective structures with both band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…But it is very challenging to achieve compactness in curved FSS. Some research on curved FSSs have been done …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But it is very challenging to achieve compactness in curved FSS. Some research on curved FSSs have been done …”
Section: Introductionmentioning
confidence: 99%
“…There was no measured result for ratification. Begam et al demonstrated broadband (up to 19.45 GHz) and multiresonating frequencies in simulated transmission characteristics by designing fractal semicylindrical FSSs loaded with Koch snowflake and Vicsek fractal elements it was illustrated that 1 GHz transmission band was obtained in Y slot‐loaded curved FSS.…”
Section: Introductionmentioning
confidence: 99%